Fundraising for social change - Klein, Kim (Kim Klein's Fundraising series, 2011)
"Fundraising for Social Change is one of the most widely used books on fundraising in the U.S. This, the sixth edition, is thoroughly revised and updated. It includes hands-on, practical strategies and accessible techniques for both practitioners and activists who want their organizations to grow and thrive. It includes a broad range of topics that have made the book a classic, such as asking for money, planning and conducting major gifts campaigns, using direct mail effectively, conducting capital and endowment campaigns, using the Internet, the relationship between the development director and the executive director, and making a career of social change fundraising"--Provided by publisher.